PENGEMBANGAN PROGRAM PELATIHAN KEPRAMUKAAN GOLONGAN PENEGAK PADA MAHASISWA PENDIDIKAN GURU MADRASAH IBTIDAâ€™YAH IAIN PONTIANAK - Komalasari, Komalasari; Komalasari, Aunurrahman; Usman, Andi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis Development of Scouting Training Program of Enforcement Group for students of School Teacher of Madrasah Ibtida'yah Department of IAIN Pontianak is based on the low ability and skill of students in understanding scouting concept which refers to General Skill Requirements (SKU) and Special Skills Requirements (SKK). The objective of Development of Scouting Training Program of Enforcement Group is to produce a curriculum that can be used independently through training activities that are expected to assist the students in understanding the concept of scouting in accordance with the SKU and SSK effectively.The development model used in this Thesis uses a PLOMP model that has 5 stages: 1). Preliminary Investigation Phase 2). Design Phase 3. Realization/ Construction Phase 4). Test, Evaluation and RevisionPhase and 5). Implementation Phase. The results of the Thesis showed that the classes of design of the scouting training programconsisted of (1) Analysis of students (learners / scouts), materials and tasks (2) Implementation of enforcement scouting training program (3) Result of skill practice from the enforcement scouting training program on students. The development phase of the module begins with the preparation of weekly, monthly training program, materials and training media as well as media review and materials by experts showing media and materials have met the eligibility criteria for field trials, 35 students who show positive response (interested) in attending the scouting activity of the enforcement group. Obtaining the results of student practice after following shows that students can easily understand the concepts and skills of students in completing SKU.Â Keywords: Development, Training Program, Scouting, Enforcement Group, PLOMP Model.